Identification and assessment of stress and associated stressors among veterinary students in India using a cross-sectional questionnaire survey - Grakh, Kushal; Panwar, Diksha; Jadhav, Vijay Jayawant; Khurana, Rajesh; Yadav, Dheeraj; Bangar, Yogesh Chandrakant; Singh, Lokender; Chahal, Niharika; Kumar, Kamal (Frontiers in Public Health, 2022)
Veterinary education, is a rigorous professional training program, which exposes students to significant academic and non-academic pressures. The identification of stressors and stress levels among veterinary students mighty help the designing and implementation of coping strategies to protect the students' mental health. A 44-item based cross-sectional questionnaire survey was prepared and disseminated among veterinary students in India to identify the stressors responsible, measure the amount of stress, and relate stress to characteristics like gender, degree year, and family income. A total of n=611 veterinary students across 14 states including 27 colleges/universities participated in the study. The collected data was evaluated for sampling adequacy, construct validity, and reliability using a set of statistical tests. The analysis revealed high sampling adequacy with a KMO value of 0.957 and a highly significant anti-image correlation (p<0.001). The principal component analysis generated six factors or subscales which effectively explained 51.98% of the variance in the data, depicting high construct validity. The Cronbach’s alpha value of 0.957 revealed high internal consistency for the questionnaire. Analysis revealed more than 94% of pupils under stress, with levels ranging from moderate to severe. Academic-related stress (95.58%) was the leading cause of overall stress in the present study followed by inter- and intrapersonal and career related-stressors (93.12%) and exams and evaluation-related stress (90.99%). In comparison to male students, female students reported significantly higher levels of overall stress, academic stress, and intrapersonal and interpersonal stress (p<0.001) using Chi-square. The students from lower-income families experienced significantly higher overall stress as well as stress due to family responsibilities (p<0.001). The first-year undergraduate students reported significantly higher (p<0.001) stress due to family responsibilities-related stressors whereas second-year students due to social activities-related stressors. The hierarchal regression model predicted that gender, family income, academic-related stressors, inter- and intrapersonal and career-related stressors, and social activities-related stressors can be employed to evaluate overall stress among students, as they ensured the maximum variance in the data (p<0.001). To the best of our knowledge, this is the first Indian study to identify stressors, quantify associated stress and predict major attributes to be targeted in future studies for veterinary students.